Modulation of GABA and glutamate release by brain-derived neurotrophic factor : role of adenosine A2A receptors - Parreira, Sara Luísa dos Santos Bragança (2016)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2014